Synthesis of g-C3N4/WO3-carbon microsphere composites for photocatalytic hydrogen production. (28th February 2022) - Sun, Meng; Zhou, Yunlong; Yu, Teng; Wang, Jian
Abstract: In this paper, a g-C3 N4 /WO3 -carbon microsphere composite-based photocatalyst was successfully prepared by a one-pot thermal synthesis method for sunlight driven decomposition of water to produce hydrogen. The results show that the g-C3 N4 /WO3 -carbon microspheres had better photocatalytic properties and stability. Under visible light and sunlight irradiation, the hydrogen production efficiency of the photocatalytic decomposition of water was 107.75 times and 70.54 times greater than that of pure g-C3 N4, respectively. The experimental and characterization results show that g-C3 N4 and WO3 formed a Z-scheme heterojunction on the surface of the g-C3 N4 /WO3 -carbon microsphere composite-based photocatalyst. Carbon microspheres modified on g-C3 N4 nanosheets and WO3 had good conductivity and promoted the transfer of photogenerated electrons in g-C3 N4 nanosheets. The addition of carbon microspheres increased the specific surface area of the composite photocatalyst. The g-C3 N4 /WO3 -carbon microsphere composite-based photocatalyst showed strong adaptability to the fluctuating light intensity, providing feasibility for industrialized mass production. Graphical abstract: Image 1 Highlights: g-C3 N4 /WO3 -carbon microsphere composites were prepared. The g-C3 N4 /WO3 -carbon microsphere composites exhibited high hydrogen production. The synergy of g-C3 N4 /WO3 and carbon microspheres improved the catalytic activity. The biomass carbon microsphere increased the electron transfer rate of composites.